2001
DOI: 10.1677/joe.0.1700555
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the effects of tamoxifen, toremifene and raloxifene on enzyme induction and gene expression in the ovariectomised rat uterus

Abstract: This study compares the actions of oestradiol, tamoxifen, toremifene and raloxifene on enzyme and gene expression in uterine tissues of ovariectomised rats over 72 h. The time-course for the induction of ornithine decarboxylase by the compounds showed a rapid biphasic response, while for creatine kinase brain type (BB) there was a continued increase over 72 h. The efficacy of induction showed that, with both markers, oestradiol gave the highest induction level, followed by tamoxifen or toremifene and then ralo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 38 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Numerous responses were observed that agree well with published data, as described in the DISCUSSION. However, there were also several well-established estrogen-regulated responses not observed in this study, including Cdk5 (p1z ϭ 0.130) (3), Ccnd3 (p1z ϭ 0.997) (3,25), estrogen-responsive finger protein (Trim25; p1z ϭ 0.999) (50), Rb1 (p1z ϭ 0.559) (27), and syndecan 3 (Sdc3; p1z ϭ 0.248) (63). In several cases, they were associated with low p1z values or lacked a significant treatment-by-time interaction ANOVA term, and in some cases these were considered absent by the MAS5 software.…”
Section: Responses Not Observedmentioning
confidence: 49%
“…Numerous responses were observed that agree well with published data, as described in the DISCUSSION. However, there were also several well-established estrogen-regulated responses not observed in this study, including Cdk5 (p1z ϭ 0.130) (3), Ccnd3 (p1z ϭ 0.997) (3,25), estrogen-responsive finger protein (Trim25; p1z ϭ 0.999) (50), Rb1 (p1z ϭ 0.559) (27), and syndecan 3 (Sdc3; p1z ϭ 0.248) (63). In several cases, they were associated with low p1z values or lacked a significant treatment-by-time interaction ANOVA term, and in some cases these were considered absent by the MAS5 software.…”
Section: Responses Not Observedmentioning
confidence: 49%
“…Similarly, gene expression analysis can provide insight into the physiological processes regulated by hormones in their target organs. Complementary DNA (cD NA) microarray technology has been used to investigate estrogen action in breast cancer cells and in the uterus [265,266], thyroid hormone action in the liver [267], and androgen action in normal and pathological conditions in the prostate [268].…”
Section: Cdna Microarray Technology For Gene Expression Profilingmentioning
confidence: 99%
“…2007). Only a few studies to date have examined in detail the global gene expression changes in the uteri of mice or rats in response to an ESR-specific SERM (Green et al . 2001, Hewitt et al .…”
Section: Introductionmentioning
confidence: 99%